Considerazioni preliminari sull’arte del delegare. Sol Lewitt e Bruce Nauman alla Biennale di Tokyo del 1970: due casi studio - Charans, Eleonora (Venezia Arti, 2014)
Within Conceptual Art attitudes and processes, artists sometimes delegate the execution of an artwork – more or less performative – to a third party through instructions, written or drawn. The following contribution focuses on two specific events, respectively conceived by Sol LeWitt and Bruce Nauman, for the same show – the Tokyo Biennale organized in 1970. What is intended to analyze is the crucial role played by instructions and their importance for future museological reconstructions, when the artist is not present or no longer alive.